Gene expression and polymorphisms of toll-like receptor 8 among Iraqi COVID-19 patients - Hussein, Raheem M.; Fadhil, Hula Y.; Alwan, Ali Hussein (Iraqi Journal of Science, 2025)
Toll-like receptors trigger both innate and adaptive immune responses against viral infections by inducing the release of inflammatory cytokines and antiviral mediators. This study aims to examine the role of TLR8 and genetic variants thereof in the progression and recovery of COVID-19 disease. It was conducted on 90 patients, (including 45 severe-critical cases, 45 mild-moderate cases),50 recovered cases, and 89 healthy people using quantitative real-time and allele-specific PCR for gene expression and gene polymorphisms determination, respectively. TLR8 gene expression did not show a significant difference among the study groups, while its median level showed statistically significant differences with respect to disease severity and Ct values. Interestingly, it showed a negative correlation with respect to the concentrations of some clinical parameters, which constituted a significant difference with respect to C-reactive protein and lactate dehydrogenase. However, in COVID-19 patients, low frequencies of the TLR8 G and C alleles of rs3764879 in male patients and the G allele of rs3764880 in female patients were seen. Additionally, the A allele of rs37648801 in male patients and the A allele and its AA genotype in female patients increasingly affected their frequency. An association between males and females regarding increased frequency of the A allele of rs3764880 in patients and the G allele of rs3764880 in healthy subjects, constituting a risk factor and a protective factor, respectively, in both sexes. The frequency of certain alleles was found to be associated with either increased or decreased susceptibility to COVID-19 infection and severity. However, the TLR family has been shown to exhibit a particular kind of extremely accurate gene regulation.